A new [Co21(H2O)4(OH)12]30+ unit-incorporating polyoxotungstate for sensitive detection of dichlorvos. (24th June 2020) - Shi, Dongying; Cui, Chao-Jie; Sun, Chun-Xiao; Du, Jun-Ping; Liu, Chun-Sen
Abstract : A new [Co21 (H2 O)4 (OH)12 ] 30+ unit-incorporating polyoxotungstate (denoted as Co25 Si6 W60 ) has been hydrothermally synthesized and fully characterized. The unique Co25 Si6 W60 -based biosensing system offers an environmentally-friendly route for detecting dichlorvos. Abstract : A new [Co21 (H2 O)4 (OH)12 ] 30+ unit-incorporating polyoxotungstate, Na18 [Co(H2 O)6 ]2 {[Na(H2 O)4 ]2 [Na(H2 O)2 ]2 [Co(H2 O)3 ]2 [Co21 (H2 O)4 (OH)12 ](SiW10 O37 )6 }·24H2 O (denoted as Co25 Si6 W60 ), has been hydrothermally synthesized and fully characterized via elemental analyses, thermogravimetric analysis, bond valence sum (BVS) calculations, IR spectrum, UV-vis spectrum, diffuse reflectance spectrum, powder X-ray diffraction and single-crystal structural analysis. The most remarkable feature is that the gigantic [Co21 (H2 O)4 (OH)12 (SiW10 O37 )6 ] 30− core in Co25 Si6 W60 is composed of a square-like [Co21 (H2 O)4 (OH)12 ] 30+ nanosheet encapsulated by six dilacunary Keggin [α-SiW10 O37 ] 10− moieties in a staggered fashion, resulting in a remarkable sandwich-type assembly. Furthermore, the unique Co25 Si6 W60 -based biosensing system, as a simple, rapid, and highly sensitive electrochemical platform, offers an environmentally friendly route for detecting dichlorvos in the field of both food safety and environmental pollution.